Patient-Provider Relationships Across the Transition From Pediatric to Adult Diabetes Care: A Qualitative Study. (January 2014) - Ritholz, Marilyn D.; Wolpert, Howard; Beste, Meg; Atakov-Castillo, Astrid; Luff, Donna; Garvey, Katharine C.
Purpose: The purpose of this study was to explore perceptions that emerging adults with type 1 diabetes (T1D) have of their patient-provider relationships across the transition from pediatric to adult care. Methods: Twenty-six emerging adults with T1D (mean age 26.2 ± 2.5 years) participated in 5 focus groups stratified by current level of glycemic control (A1C). Coded audio-recorded data were analyzed using thematic analysis and aided by NVivo software. Results: Three major themes emerged from the analysis: (1) loss and gain in provider relationships across the transition—patients expressed 3 key responses to leaving pediatric providers that differed by A1C levels: sad reluctance and "natural progression" (mean A1C ± SD 7.4% ± 0.6%) and wanting to go (mean A1C ± SD 9.8% ± 1.0%); (2) partners in care versus on one's own—patients valued how adult providers' collaborative conversations promoted their involvement and accountability compared to "parent-centric" interactions with pediatric providers, but they also expressed ambivalence over increased independence in adult care; (3) improving provider approaches to transition—patients recommended that pediatric providers actively promote emerging adults' autonomy while maintaining parental support, communication with adult providers, and follow-up with transitioning patients. Conclusions: Findings highlight the importance of enhanced provider awareness of T1D emerging adults' complex feelings about the transition in care. Improved integration of individual- and family-centered approaches to developmentally tailored diabetes care is needed to augment patient and provider relationships.